Sustainability Analysis of Subscription Economy Business Model on Platform Streaming Amidst Fierce Competition - Mar'atus Solikhah (International Journal of Social Research, 2026)
The development of the digital economy has driven the adoption of the subscription economy as a primary revenue source for streaming platforms. This model offers revenue stability through recurring payment mechanisms, but amidst increasingly fierce competition between platforms, the sustainability of the subscription business model faces serious challenges. High churn rates, content homogeneity, and increasing user price sensitivity demand more adaptive and long-term sustainability strategies. This study aims to analyze the factors influencing the sustainability of the subscription business model on streaming platforms amidst intense competition, with a focus on customer retention, perceived value, pricing strategy, content differentiation, and user experience. This study uses a quantitative approach with an explanatory design. Data were collected through an online survey of active users of subscription-based streaming platforms using a purposive sampling technique. Data analysis was performed using the Structural Equation Modeling method using the Partial Least Squares (SEM-PLS) approach. The results show that customer retention is the most dominant factor in maintaining the sustainability of the subscription business model. In addition, perceived value, adaptive pricing strategy, content differentiation, and user experience have a significant influence on reducing churn and increasing customer loyalty, thus supporting the sustainability of streaming platforms.